The Relationship Between Family Involvement and Satisfaction Level of The Family of Critical Care Patients in The Sumber Waras Hospital - Indah Purnama Sari; Mochamat Helmi; Wiyarni Pambudi; Ernawati Ernawati (Asian Journal of Social and Humanities, 2023)
The average trend of intensive care unit (ICU) patients increases every day across the globe, including in Indonesia. Patients and their families have various needs during intensive care in the ICU. Based on these needs, we classify them into care, hope, information, participation, and assurance. In order to fulfill these needs, support and involvement of family members are needed. If the needs are fulfilled, this will have an effect on the satisfaction of family members. Therefore, this study aims to investigate the relationship between family involvement and family satisfaction of critical patients in Intensive Care Unit of Sumber Waras Hospital, West Jakarta. Descriptive and analytic research design with a quantitative approach is used in this study. Samples were collected using a consecutive sampling method and a questionnaire was used as a data collection instrument. Pearson Chi-Square correlation test was performed to determine the relationship among variables. This study showed the average scores of family involvement and family satisfaction were 4.0-4.3 out of 5 on a Likert scale. From 49 respondents, 29 respondents had a higher level of involvement in information and 34 respondents had a higher level of satisfaction in assurance. Family involvement in care, hope, information, participation, and assurance had a significant positive association with family satisfaction, with the effect exerted at 42%, 56%, 51%, 49%, and 49%, respectively. From this study, we can conclude that the patient’s family members had a moderately to very high level of involvement and satisfaction. There is a significant positive association between family involvement and family satisfaction in the Sumber Waras Hospital, West Jakarta.